2018
DOI: 10.1136/bcr-2017-221854
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic use of intermittent fasting for people with type 2 diabetes as an alternative to insulin

Abstract: This case series documents three patients referred to the Intensive Dietary Management clinic in Toronto, Canada, for insulin-dependent type 2 diabetes. It demonstrates the effectiveness of therapeutic fasting to reverse their insulin resistance, resulting in cessation of insulin therapy while maintaining control of their blood sugars. In addition, these patients were also able to lose significant amounts of body weight, reduce their waist circumference and also reduce their glycated haemoglobin level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 10 publications
0
78
0
8
Order By: Relevance
“…In 2017, a trial reported that T2D remission is possible through dietary weight management administered systematically by a primary health-care team [ 30 ]. Since then, additional studies showed that primary care-led, physician-involved, dietary and lifestyle interventions can effectively treat and reverse type 2 diabetes and associated comorbidities [ 30 , 31 , 32 , 33 , 34 , 35 ]. Many of these studies used a low-carbohydrate, high-fat diet that is currently neither approved nor consistently advocated by the Department of Agriculture, the Food and Drug Administration, the American Heart Association, the American Diabetes Association, or the Academy of Nutrition and Dietetics.…”
Section: Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, a trial reported that T2D remission is possible through dietary weight management administered systematically by a primary health-care team [ 30 ]. Since then, additional studies showed that primary care-led, physician-involved, dietary and lifestyle interventions can effectively treat and reverse type 2 diabetes and associated comorbidities [ 30 , 31 , 32 , 33 , 34 , 35 ]. Many of these studies used a low-carbohydrate, high-fat diet that is currently neither approved nor consistently advocated by the Department of Agriculture, the Food and Drug Administration, the American Heart Association, the American Diabetes Association, or the Academy of Nutrition and Dietetics.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Physicians are trained to treat complications arising from obesity, such as heart disease and T2D, but medical school curriculum emphasizes much less on the utilization of nutritional interventions to mitigate the risks of developing those complications in the first place [ 39 , 40 ]. As discussed earlier in the article, only recently has there been compelling evidence that primary care physician-led dietary interventions can effectively treat and reverse metabolic diseases [ 30 , 31 , 32 , 33 , 34 , 35 ]. More commonly, unless drugs or surgical interventions are considered, patients are referred to retail programs run by registered dieticians and health coaches to deal with body weight problems.…”
Section: Rethinking Strategiesmentioning
confidence: 99%
“…Randomized trials demonstrate that intentional weight loss reduces type 2 diabetes, retards aging-related functional decline; and increases cognitive and physical function; and increases lifespan [5] . Modest weight losses of 5%-10% have been associated with LETTER TO THE EDITOR significant improvements in cardiovascular disease risk factors (i.e., decreased HbA1C levels, reduced blood pressure, increase in HDL cholesterol, decreased plasma triglycerides) in patients with T2D [6] . In addition to the weight loss effects and metabolic improvements, several other beneficial effects of therapeutic fasting have been described including improvements in lipid profiles, osteoarthritis, healing of thrombophlebitis, healing of refractory dermal ulcers and tolerance of elective surgery [7] .…”
Section: Letter To the Editormentioning
confidence: 99%
“…Diabetes type 2 (dm) case series have demonstrated the effectiveness of therapeutic fasting to reverse insulin resistance, with resultant cessation of insulin therapy, accompanied by reduction in body fat, weight circumference and glycated haemoglobin level. 29 Though not directly related, improved glycemic contol and associated weight loss may also support a response to prolotherapy treatments. There are over 100 known physiologic factors contributory to wound healing deficiencies in diabetes, such as impairment of growth factor production, 30 32 .…”
Section: Introductionmentioning
confidence: 99%